Analysing cold-climate urban heat islands using personal weather station data - Jonathon Taylor; Charles H. Simpson; Jaana Vanhatalo; Hasan Sohail; Oscar Brousse; Clare Heaviside (Buildings & Cities)
Urban heat islands (UHI) modify building heating and cooling loads and public exposure to non-optimal temperatures, topics of increasing importance given climate change. This study uses personal weather stations (PWS) to investigate urban temperatures in Helsinki, Espoo, Vantaa and Tampere, Finland. Data from PWS within 50 km of municipal boundaries were acquired, cleaned and spatially linked to socio-economic, land-use and local climate zone (LCZ) classifications. Analyses evaluated for PWS location bias, including distributions across socio-economic and land-use categories. Temperatures were examined across LCZs and the urban influence on temperature, heating degree-days (HDD), cooling degree-days (CDD) and number of extreme hot or cold days calculated. Results indicate more PWS in residential open low-rise areas, but no consistent biases across incomes or ages. UHI intensities were, on average, 1.2°C (interquartile range (IQR) = 0.6–1.2°C) for Helsinki, 0.8°C (IQR = 0.4–1.2°C) for Espoo, 0.7°C (IQR = 0.4–1.1°C) for Vantaa and 0.5°C (IQR = 0.1–0.8°C) for Tampere, with differences greatest during spring and summer. Urban PWS have 112–281 fewer HDD and 30–50 more CDD than rural equivalents, suggesting a net benefit of the UHI for building energy consumption. Urban intensification of extreme heat was greater than extreme cold reduction. Practice relevance Urban climate research typically relies on sparse networks of official or researcher-deployed weather stations, interpolations thereof, land-surface temperature observations or urban climate models. However, PWS provide an additional, emerging source of data. In Finland, relatively dense and uniform PWS coverage provides opportunities to evaluate land-use impacts on urban temperatures, energy and population temperature exposures. Elevated temperatures from the UHI effect in Helsinki, Vantaa, Espoo and Tampere lead to a reduction in annual HDD around four to five times greater than the increase in CDD, as well as reduced exposure to extreme cold. Adaptation actions that aim to reduce the UHI and mitigate climate-related heat risks in colder climates may have the disbenefit of increasing energy consumption if temperature reductions also occur during heating seasons. Therefore, for cities in the far north, dynamic or seasonal adaptations such as building cooling or seasonal greenery may be preferable.